Striatal cholinergic interneurons regulate cognitive and affective dysfunction in partially dopamine‐depleted mice. (8th October 2018) - Ztaou, Samira; Lhost, Juliette; Watabe, Isabelle; Torromino, Giulia; Amalric, Marianne
Abstract: Early non‐motor symptoms such as mood disorders and cognitive deficits are increasingly recognised in Parkinson's disease (PD). They may precede the characteristic motor symptomatology caused by dopamine (DA) neuronal loss in the substantia nigra pars compacta (SNc). It is well known that striatal cholinergic interneurons (ChIs) are emerging as key regulators of PD motor symptom, however, their involvement in the cognitive and affective alterations occurring in the premotor phase of PD is poorly understood. We used optogenetic photoinhibition of striatal ChIs in mice with mild nigrostriatal 6‐hydroxydopamine (6‐OHDA) lesions and assessed their role in anxiety‐like behaviour in the elevated plus maze, social memory recognition of a congener and visuospatial object recognition. In transgenic mice specifically expressing halorhodopsin (eNpHR) in cholinergic neurons, striatal ChIs photoinhibition reduced the anxiety‐like behaviour and reversed social and spatial short‐term memory impairment induced by moderate DA depletion (e.g., 50% loss of tyrosine hydroxylase TH‐positive neurons in the SNc). Systemic injection of telenzepine (0.3 mg/kg), a preferential M1 muscarinic cholinergic receptors antagonist, improved anxiety‐like behaviour, social memory recognition but not spatial memory deficits. Our results suggest that dysfunction of the striatal cholinergic system may play a role in the short‐term cognitive and emotional deficits of partially DA‐depleted mice. Blocking cholinergic activity with M1 muscarinic receptor antagonists may represent a possible therapeutic target, although not exclusive, to modulate these early non‐motor deficits. Abstract : Optogenetic photoinhibition of striatal cholinergic interneurons (ChIs) reduced anxiety‐like behaviour and reversed social memory recognition of a congener and visuospatial object recognition in mice with moderate nigrostriatal dopamine lesions, a model of prodromal phase of Parkinson's disease (PD). Telenzepine (0.3 mg/kg), a preferential M1 muscarinic cholinergic receptors antagonist, improved anxiety‐like behaviour, social memory recognition but not spatial memory deficits. Striatal ChIs could contribute to cognitive and anxiety symptoms in a partial dopamine depletion mice model of early PD, when motor symptoms are not manifest. M1 muscarinic receptor antagonists may represent a possible therapeutic target, among others, to counteract these symptoms.